Hubungan pengetahuan dan sikap perawat rawat inap dengan upaya pencegahan dan penanggulangan kebakaran di RSU Mitra Medika Tanjung Mulia - Salmira, Cut Saura; Najihah, Khoirotun; Amalia, Nur (Journal of Pharmaceutical and Sciences, 2023)
There is a possibility of work accidents at hospitals., especially fires. Ionizing radiation, chemicals, and medicinal gases are flammable elements that pose a significant fire risk. The observation's findings revealed that at Mitra Medika Tanjung Mulia Hospital, small extinguishers for fires of the dry chemical powder type and fire extinguishers for CO2, emergency stairs, routes for evacuation, and assembly points were available. However, some nurses continued to lack the knowledge necessary to utilize them. This study investigates factors associated with inpatient nurses' preventive efforts at Mitra Medika Tanjung Mulia Hospital. This cross-sectional study employs a quantitative methodology. There were 90 participants in the study, all nurses, and a purposive sampling technique was used to select a sample size of 35 participants. The chi-square test statistic is used in data analysis. According to the study, attitude has a p = 0.009 < 0.05, and knowledge has a p = 0.017 < 0.05. Based on these findings, Mitra Medika Tanjung Mulia Hospital's knowledge and attitudes regarding fire prevention. According to the study's findings, Mitra Medika Tanjung Mulia Hospital's fire prevention is influenced by certain factors. Hospitals should consider teaching all their nurses about fire safety so that they are well-versed in the subject and can prevent fires in medical facilities.